5x + 4
5x + 6 = 31 5x = 31 - 6 5x = 25 x = 5 So the equation is equal.
x is greater than or equal to 5.
if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7
5x-2x = 3
3(x + 7) > 5x - 13 3x + 21 > 5x - 13 - 2x > -34 or 2x < 34 so that x<17
5x+2x=7x2x + 5x = 7x
5x - 2x = 3x
f(x) = (2x - 3x2)/(-5x - 6)f(x) = -(3x2 - 2x)/-(5x + 6)f(x) = (3x2 - 2x)/(5x + 6)5x + 6 = 05x + 6 - 6 = 0 - 65x = -65x/5 = -6/5x = -6/5 (the vertical asymptote of f)Since the degree of the polynomial function in the numerator is greater than the degree of the polynomial function in the denominator, then the graph of f has no horizontal asymptote.
5x * 2x = 10x^2
(2,7)
5